Bilateral huge fimbrial cysts with torsion of right fallopian tube - Rijal, P; Pokharel, H; Chhetri, S; Pradhan, T; Agrawal, A (Health Renaissance, 2012)
A case of bilateral fimbrial cyst with torsion of right side is presented, occurring in a 32 year old female. She presented in outpatient department with pain abdomen and feeling of mass in lower abdomen since six months. Initial assessment of ovarian cyst was made. Ultrasound showed cystic structures in left adnexa and complex cyst in right adnexa. Laprotomy was performed and bilateral fimbrial cysts in fallopian tubes were identified with torsion on right side which was subsequently confirmed on histopathology. Although huge fimbrial cysts with torsion of fallopian tube is rare, it should be considered in differential diagnosis of abdominal mass with pain in females. DOI: http://dx.doi.org/10.3126/hren.v10i2.6588 Health Renaissance 2012; Vol 10 (No.2); 153-154